2009
DOI: 10.1075/cilt.307.04fri
|View full text |Cite
|
Sign up to set email alerts
|

The adaptation of Romanian loanwords from Turkish and French

Abstract: This paper examines several factors affecting loanword adaptation, using a data set of Romanian loanwords from Turkish and French. After exploring the position of loanwords in the lexicon and the nature of the two contact situations, the author considers relevant social, morphological, and phonological factors. First is the difference in the loanwords’ semantic domains and their motivations for being borrowed. Next, the author introduces the morphophonological factors considered—stress, desinence class, and ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 0 publications
0
16
0
1
Order By: Relevance
“…Moreover, the phonology of loanwords is affected by extragrammatical factors and two of these factors are of particular relevance here. First, despite the standard view of phonology as a system independent of orthography, it has been demonstrated that loanwords are particularly exposed to the influence of spelling, as they are -more than native words -transmitted and learned in writing (Smith, 2006;Friesner, 2009;Escudero and Wanrooij, 2010;Molęda, 2011). Second, the adaptation of words borrowed from a particular language is at least partly conditioned by the status of this language and the knowledge of this language in the target population (Kang, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the phonology of loanwords is affected by extragrammatical factors and two of these factors are of particular relevance here. First, despite the standard view of phonology as a system independent of orthography, it has been demonstrated that loanwords are particularly exposed to the influence of spelling, as they are -more than native words -transmitted and learned in writing (Smith, 2006;Friesner, 2009;Escudero and Wanrooij, 2010;Molęda, 2011). Second, the adaptation of words borrowed from a particular language is at least partly conditioned by the status of this language and the knowledge of this language in the target population (Kang, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…the preservation of original pronunciation), is that the ability to accurately pronounce a foreign structure is not sufficient in explaining the choice between these two integration strategies (e.g. Aktürk-Drake, 2011, 2014; Friesner, 2009a; Paradis & LaCharité, 1997, 2008; Poplack et al, 1988). Even when borrowers have the necessary linguistic competence in the donor language (which is often a second or foreign language), they are sometimes known to alter their pronunciation when they produce the same word as a loanword in their first language (L1) (Aktürk-Drake, 2014; Friesner, 2009b).…”
Section: Introductionmentioning
confidence: 99%
“…Also, given the same two languages, depending on the sociolinguistic circumstances of the contact and the channel of borrowing, the outcome of adaptation can differ significantly (Yip 2002, Smith 2006, Heffernan 2007, Friesner 2009a, Y. Kang, forthcoming). Moreover, adaptations of both types – phonological and phonetic – are often attested within a single contact situation (Friesner 2009a, b, Chang, to appear, Y. Kang, forthcoming). In other words, there is growing awareness of the multi-faceted nature of loanword phenomena in the field, and in order to gain a comprehensive understanding of loanwords, it is informative to examine how adaptation forms are transmitted through the community (cf.…”
Section: Introductionmentioning
confidence: 99%